Experiencia moral y acción comunicativa - Giannini, Humberto; Fuentes, Juan José; Hamamé, Eva; Álvarez, Isabel; Gardella, Nicole (Revista de Filosofía, 2008)
Communication refers to the category of action, but it is not directed to the world immediately. Instead, it is oriented to elicit a certain type of answer from somebody else. This constrained field -domain of the human interaction- is the particular subject of Ethics.